Confirmed and potential wild hosts of the Spotted wing drosophila (Drosophila suzukii) in Slovenia - De Groot, Maarten (Acta entomologica slovenica (Ljubljana), 2020)
The spotted wing drosophila (Drosophila suzukii (Matsumura)) is a highly invasive species and attacking different species of berry carrying hosts. Much research has already been done on the crop hosts over the world and in Slovenia, but for wild hosts less is known. On basis of literature and fieldwork we prepared a list of potential and actual known species of wild hosts for Slovenia. In 2019, berries of different species were collected and D. suzukii was either reared from these berries or berries were dissected. In total we found in the literature for Europe 99 species which were used as host for D. suzukii. For Slovenia we found 71 potential hosts and 14 hosts which were actually infested. in Slovenia there was a broad range of potential hosts from 41 genera. The genera with the most potential hosts were Prunus, Lonicera and Vaccinium. Among the potential hosts were also many species which were invasive alien or alien species. The list was discussed in the context of management implications and further research on D. suzukii in Slovenia.
Keywords: berries; divji gostitelji; Drosophila suzukii; forests; gozdovi; Insecta; jagodičje; mušice; pest control; plodove vinske mušice; potencialni gostitelji; potential hosts; Slovenia; Slovenija; spotted wing drosophila; wild hosts; zatiranje; Žuželke